Unconventional Resources Technology Conference 2015
DOI: 10.2118/178583-ms
|View full text |Cite
|
Sign up to set email alerts
|

When Less Flowback Is More: A Mechanism of Permeability Damage and its Implications on the Application of EOR Techniques

Abstract: Only a small fraction of fracturing fluid is recovered as flowback after hydraulic stimulation of low permeability formations. From the point of view of relative permeabilities, the minimization of fracturing fluid losses is desirable to maximize the flow of hydrocarbon. On the other hand, field observations indicate that wells where less fracturing fluid is recovered as flowback performed better in production, leading to an apparent contradiction. We present a physics-based model that can account for both of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Those two processes have different capillary pressure curves and different irreducible water saturations (Kovscek, Wong, and Radke 1993). It has been reported that in some reservoirs, a period of well-resting after hydraulic fracturing treatment can assist to improve early hydrocarbon production, which has been explained by the mixed-wettability of the reservoir (Bertoncello et al 2014;Longoria et al 2015). In Bertoncello's work, a pore scale model with small oil-filled water-wet pores and large oil-filled oil-wet pores is proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those two processes have different capillary pressure curves and different irreducible water saturations (Kovscek, Wong, and Radke 1993). It has been reported that in some reservoirs, a period of well-resting after hydraulic fracturing treatment can assist to improve early hydrocarbon production, which has been explained by the mixed-wettability of the reservoir (Bertoncello et al 2014;Longoria et al 2015). In Bertoncello's work, a pore scale model with small oil-filled water-wet pores and large oil-filled oil-wet pores is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…However, this model might not be valid because if small pores are filled with oil, the wettability of small pores are more prone to be altered to oil-wet (Kovscek, Wong, and Radke 1993). In Longoria's study (Longoria et al 2015), water redistribution from near fracture area to the area away from fracture is considered. However, the mixed-wettability properties were not fully considered.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, improvements in hydrocarbon permeability have been observed in field operations after performing well shut-ins (Bertoncello et al, 2014). Furthermore, several studies have shown that well shut-ins after the hydraulic stimulation can dissipate the water into deeper regions of the formation rock (Almulhim et al, 2014;Bertoncello et al, 2014;Cheng, 2012;Dutta et al, 2014;Mahadevan and Sharma, 2005;Longoria et al, 2015). However, the efficacy of a well shut-in depends on the petrophysical properties of the reservoir and a recent laboratory study showed that some reservoir samples regain permeability to the hydrocarbon after a shut-in while others do not (Bostrom et al, 2014).…”
Section: Introductionmentioning
confidence: 99%